Therapeutic use exemptions (TUEs) at the Olympic Games 1992-2012 - Fitch, K. D. (British Journal of Sports Medicine, 2013)
The need for therapeutic use exemptions (TUEs) or the permitted use of Prohibited Substances and Prohibited Methods by athletes to treat significant medical conditions arose when several classes of drugs used commonly in medicine were prohibited in sport by the International Olympic Committee (IOC) during the 1980s. However, although the IOC Medical Commission (IOC-MC) gave qualified support for the concept to formally start at the 1992 Barcelona Olympics, the Commission's fears that athletes might abuse the mechanism resulted in minimal publicity and its non-inclusion in the Medical Code of the Olympic Movement for 8 years. TUEs would not be widely publicised until the advent of the World Anti-Doping Agency which not only approved the principles of TUEs as developed by the IOC's Medications Advisory Committee (MAC) in 1991, but also introduced the name of TUE. Several changes to the Prohibited List have resulted in TUEs being necessary for substances that were permitted 20 years ago as disclosed in a review of TUEs approved at the 11 Olympic Games that the IOC's MAC, later the TUE Committee (TUEC), has operated. The IOC and its TUEC played a pivotal role in developing the concept of TUE which is now globally accepted.